Box–Behnken Design: Wet Process Optimization for Saponins Removal From Chenopodium quinoa Seeds and the Study of Its Effect on Nutritional Properties - El Hazzam, Khadija; Mhada, Manal; Metougui, Mohamed Louay; El Kacimi, Kamal; Sobeh, Mansour; Taourirte, Moha; Yasri, Abdelaziz (Frontiers in Nutrition, 2022)
The pseudocereal grain, Quinoa (Chenopodium quinoa Willd.), has a great nutritional value due to its high contents of proteins, fiber, minerals, and vitamins. However, saponins naturally present outside the grains represent an obstacle to their consumption as human food. Before consumption, the grains are subjected to various treatments, which alter their nutritional value. In an attempt to eliminate the maximum of saponins using the wet process while minimizing the washing conditions and preserving the nutritional quality, we explored the effects of several parameters, including volume of water, treatment time, soaking time, number of washing, and water temperature, followed by an optimization process using Box–Behnken Design, and finally, the impact of this process on the physicochemical and techno-functional properties of six quinoa genotypes seeds was evaluated. As a result, the variation of the treatment time, volume, and temperature of the water positively affected the saponins leaching. According to the quadratic model, the maximum percentages of eliminated saponins (96.53-96.77%) were found at a temperature of 50°C, treatment times from 60 to 69 min, and water volumes from 6.99 to 7.50 mL per gram of seeds. The optimized method did not affect the proteins and microelements content (Zn, Mn, B, Mo), while a slight decrease of macro-elements (K, P, Ca, S, Mg) was noted in the level of some genotypes. On the other hand, a significant improvement of the techno-functional properties such as water and oil holding capacity was noted, with a sharp drop-in emulsifying activity in all genotypes without affecting the standard values of pH (6.4-6.8) and moisture content (10-11%) of the seeds. Hence, the optimized method showed to be a potential method for saponins removal than the currently used dry method.